Ticagrelor-based antiplatelet regimens in patients treated with coronary artery bypass grafting: a meta-analysis of randomized controlled trials. (30th September 2019) - von Scheidt, Moritz; Bongiovanni, Dario; Tebbe, Ulrich; Nowak, Bernd; Stritzke, Jan; Zhao, Qiang; Zhu, Yunpeng; Kastrati, Adnan; Cassese, Salvatore; Schunkert, Heribert
Abstract: : OBJECTIVES: The optimal antiplatelet strategy in patients undergoing CABG remains unclear. This is the first meta-analysis investigating the clinical outcomes associated with ticagrelor-based antiplatelet regimens in patients receiving CABG. METHODS: Relevant scientific databases were searched for studies investigating antiplatelet regimens after CABG from inception until April 1, 2019. Studies which randomly assigned CABG patients to either ticagrelor-based or control antiplatelet regimens were eligible. The primary outcome of this analysis was all-cause death. The main secondary outcome was MI. Other outcomes of interest were cardiac death, major adverse cardiac events, stroke and bleeding. This study is registered with PROSPERO, number CRD42019122192. RESULTS: Five trials comprising 3996 patients (2002 assigned to ticagrelor-based and 1994 to control antiplatelet regimens) were eligible for quantitative synthesis. The median follow-up was 12 months. Control antiplatelet regimens consisted of either aspirin or clopidogrel or both. As compared to control, ticagrelor-based regimens reduced the risk of all-cause death [0.61 (0.43–0.87); P  = 0.007], cardiac death [0.58 (0.39–0.86); P  = 0.007] and major adverse cardiac events [0.79 (0.63–0.98); P  = 0.03], without difference in the risk of MI [0.76 (0.50–1.18); P  = 0.22], stroke [0.99 (0.56–1.78); P  = 0.98] or bleeding [1.04 (0.95–1.14); P  = 0.41]. There was a treatment effect modification for the primary outcome associated with trials enrolling predominantly patients with acute coronary syndrome ( P for interaction = 0.038). CONCLUSIONS: In patients receiving CABG, ticagrelor-based regimens reduce mortality and major adverse cardiac events without excess bleeding risk as compared with aspirin monotherapy or the combination of aspirin and clopidogrel. The benefit of ticagrelor-based regimens is more relevant in those studies enrolling predominantly patients with acute coronary syndrome. These findings require further confirmation in randomized trials focused on this subset of patients and powered for clinical outcomes.